State of the art of business models: A bibliometric analysis - Carmo, R.; Jerónimo, C. H.; Pereira, L.; Dias, Á.; Patrício, V. (Sustainability, 2023)
Various studies have investigated the business model (BM) in different dimensions. However, bibliometric analyses in this discipline are still limited. This study aims to conduct a bibliometric analysis of business model research, identifying the state of the art, trends, and other indicators by analyzing articles published on the Web of Science (WoS) platform from 2017 to 2022. The present study examines the simultaneous occurrence of publications by year, keyword trends, bibliographic coupling, analysis of co-authorship, cities, and institutions, and finds that the literature on business models rapidly expanded between 2017 and 2020. A total of 14,881 articles were obtained as samples. The present study employs VOSviewer software to analyze the data. A considerable amount of literature has been produced on BMs, but researchers have stopped developing further literature which is thought-provoking. Based on the findings of this study, it is concluded that there is a need to research BMs in different domains such as sustainability and digitalization.